2021
DOI: 10.1016/j.jacbts.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Update on Cardioprotective Strategies for STEMI

Abstract: Highlights Beyond restoring myocardial perfusion, there is an unmet need to further reduce the size of myocardial infarctions; only 1 therapy is FDA-approved to specifically treat ischemic myocardium as an adjunct to reperfusion therapy. Here, we present the basic science and clinical studies showing that treatment with supersaturated oxygen following mechanical reperfusion therapy in patients with large anterior myocardial infarctions improves myocardial perfusion and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Exposure to hyperoxia for a short period of time before experimental ischemia induces a mild systemic oxidative stress, which induces a preconditioning-like cardioprotection, reduces the infarction area and arrhithmia [ 13 , 22 , 33 , 34 ]. In patients with ST-segment elevation myocardial infarction undergoing coronary artery stenting, infusion of supplemental oxygen directly into the left anterior descending artery (the infarct-related artery) resulted in a reduction in infarct size [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to hyperoxia for a short period of time before experimental ischemia induces a mild systemic oxidative stress, which induces a preconditioning-like cardioprotection, reduces the infarction area and arrhithmia [ 13 , 22 , 33 , 34 ]. In patients with ST-segment elevation myocardial infarction undergoing coronary artery stenting, infusion of supplemental oxygen directly into the left anterior descending artery (the infarct-related artery) resulted in a reduction in infarct size [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite positive results in preclinical models, these modalities have been largely ineffective in clinical trials. (28,31,32) Supersaturated oxygen (SSO2) therapy is the only adjunct device or drug demonstrated in an adequately powered randomized trial to reduce infarct size in STEMI patients treated with primary PCI and stenting. (33) A recent review details the effects of this therapy at the myocardial cell and microvascular level.…”
Section: Discussionmentioning
confidence: 99%
“…(33) A recent review details the effects of this therapy at the myocardial cell and microvascular level. (32) SSO2 therapy is FDA approved for intracoronary delivery after left anterior descending artery stenting for STEMI and is currently undergoing further investigation for expanded indications including in the unmet need of cardiogenic shock. Other modalities to address reperfusion injury including mechanical unloading, cooling therapies, and the delivery of other novel pharmaceutical agents require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a study regarding updates on cardioprotective strategies for STEMI was a multicenter study of 29 patients with acute STEMI reperfused with primary PCI, in which hypoxemic blood was infused for 60 to 90 min, right after proximal patency was established. The hypoxemic reperfusion was accomplished successfully in all of the patients, without therapy-related adverse events [ 62 , 105 ]. An echocardiographic study carried out on the patients showed an improvement in the wall motion score index and a trend toward an increase in mean left ventricular ejection fraction (LVEF) at 24 hours; approximately 48.6% improved immediately after angioplasty, against a 51.8% improvement after 24 hours.…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…An echocardiographic study carried out on the patients showed an improvement in the wall motion score index and a trend toward an increase in mean left ventricular ejection fraction (LVEF) at 24 hours; approximately 48.6% improved immediately after angioplasty, against a 51.8% improvement after 24 hours. After a month, the wall motion score and the LVEF improved by about 54.4%, and at 3 months it improved by 56% [ 62 ]. These clinical studies have been able to demonstrate that the SSO 2 therapy is a safe and successful agent to apply with reperfusion, in order to reduce infarct size, preserve cardiac function, reduce adverse LV remodeling, and, more likely, to improve most clinical outcomes in patients with acute anterior STEMI reperfused within 6 hours of symptoms as possible [ 62 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%